MUSICAL INSTRUMENTS USED IN 15TH- CENTURY CENTRAL ASIAN MUSIC AND THEIR PRESENT APPEARANCE - Djuraeva, Laylo (International Journal of Psychosocial Rehabilitation, 2020)
The ancient and rich musical culture of the people of Central Asia has been a powerful source of spirituality for centuries. Consequently, the 15th century is recognized as the Second Renaissance of the East as a pinnacle of national values, eternal traditions and cultural development in the long historical period. Thus, the 15th and 16th centuries belonged to the Timurid Empire, during which time the Central Asian region was a source of scientific and cultural advancement and was well recognized by the international scientific community. Along with science, culture, art, literature, architecture, craftsmanship, music has been at the highest center of attention